MAKNA KONTEKSTUAL DALAM CERPEN JEJAK PELANGI DI GUNUNG KENARI KARYA JEFTA H. ATAPENI - Karolus Budiman Jama (Jurnal Lazuardi, 2021)
This article discusses the contextual meaning contained in the short story Jejak Pelangi di Gunung Kenari by Jefta H. Atapeni. There are five contexts discussed in this article, namely social context, political context, situational context, physical context and cultural context. The purpose of this study is to describe the contextual meaning contained in the short story Jejak Pelangi di Gunung Kenari by Jefta H. Atapeni. The method used in this research is descriptive qualitative. The theory used is the sociology theory of literary works according to Wallek and Warren which focuses on the study of the relationship between literature and society. The results of this study indicate that from the five contexts, namely social context, political context, situational context, physical context and cultural context, found a social context about social care among figures, political context about political discrimination between rulers and small communities; the context of the situation about the atmosphere of anxiety, silence, happiness and emotion; the physical context of the physical violence perpetrated by the security forces against Mateu and the cultural context of marriage.